Mejoramiento del rendimiento académico de los nativos digitales en el marco del espacio europeo de educación superior (E.E.S.S.): datos de una experiencia - Calleja Reina, Marina (2014)
The digital natives or digital residents have arrived to the university, and this fact has been revealed as the necessity of transform the learning-teaching style in order to imply to the students in their own training process. In the frame of high education European space, the authors have introduced the use of self-questionnaires in order to improve the academic goals. Positive correlation has been show between quantity of questionnaires and final marks. Our results show that level of below average or failing has been reduced a 30% when this training digital tool was used. This kind of experience will be useful for another level of educational system even to other subjects with similar problems.